Dystocia in Jersey Crossbred Cow due to Schistosoma Reflexus Foetus - Mir, Asif Majeed; Baba, Firdous Ahmad; Khan, Asad (The Indian Journal of Animal Reproduction, 2025)
Dystocia or difficult birth in cattle demands urgent action due to life-threatening risks. Schistosomus reflexus (SR), a  severe fetal anomaly, results in dystocia and contributes to economic losses. A case study involving a crossbred Jersey  cow highlights prompt intervention to extract a non-viable calf with SR, emphasizing the need for careful breeding  practices and further research to manage its impact on cattle production.
Keywords: Calf; Cattle; Fetal; Manual traction; Monstority